Design of lab-scale impressed current cathodic protection (ICCP) model for steel plate buried in soil - Koh, Yee Rui, 1986-; Esah Hamzah; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2010